Dynamics of life quality perception among patients with cognitive decline during an integrated rehabilitation process - M. V. Kurmyshev; V. B. Savilov; G. P. Kostyuk (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The  article  examines  research  results  of  life  quality  perception  among  older  persons  with  mild cognitive  decline  at  the  beginning  and  at  the  end  of  the  rehabilitation  course  (intergrated  programme  of neurocognitive  rehabilitation).  This  course  is  aimed  at  improving  cognitive  functions.